FGF11 influences 3T3‐L1 preadipocyte differentiation by modulating the expression of PPARγ regulators - Lee, Kyeong Won (FEBS Open Bio, 2019)
Fibroblast growth factor 11 (FGF11) is a member of the intracellular fibroblast growth factor superfamily. Here, we identified FGF11 as a novel mediator of adipogenesis. During 3T3‐L1 adipocyte differentiation, the expression of FGF11 decreased at the mitotic clonal expansion stage and increased at the terminal differentiation stage. FGF11 knockdown reduced the expression of peroxisome proliferator‐activated receptor gamma (PPARγ), a master regulator of adipogenesis, resulting in the inhibition of adipocyte differentiation. Treatment with the PPARγ agonist rosiglitazone restored the inhibition of adipogenesis caused by FGF11 knockdown. We also report that the expression of the PPARγ regulators CCAAT/enhancer‐binding protein α, sterol regulatory element‐binding protein 1, KLF9, KLF2, GATA binding factor 2, and GATA binding factor 3 was influenced by FGF11. These results suggest that FGF11 indirectly controls the expression of PPARγ through modifying the expression of multiple PPARγ regulators, thereby mediating adipogenesis.